Build the system engineering inventory information merchandise on UD Sarua Subur branch Bangkalan - Rahman, Khalilur; Sulistiowati, Sulistiowati; Soebijono, Tony (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2014)
trade business on Sarua Subur is a distributor of bottled drinking water (AMDK), Or drink packaging in Madura. trade business on Sarua Subur has three branches, among other branches bangkalan, sumenep, Pamekkasan. trade business branch bangkalan will distribute to every store in accordance with the request of the store.During this trade business Sarua Subur branch Bangkalan Could not meet the demand a shop as much as 106(one hundred and six) The incident delay the fulfillment of customer orders every year. hence business trade Sarua Subur branch Bangkalan Need an inventory of goods which is sufficient to meet the needs of the customers In order to estimate how the number of supplies for the future trade at a venture Sarua Subur branch bangkalan It takes a system of merchandise, inventory information by applying a engineering build the system inventory information merchandise by using the method Triple eksponensial Smoothig (winters).The lateness of the problem and the fulfillment of the needs of merchandise can be taken in conclusion, that a system can be predicted an inventory of goods merchandise to UD Sarua Subur Because the system could predict supplies in the future, and also be used to memeperkirakan how the number of supplies for the moment to supply of goods in a warehouse more stable.